Why more men who have sex with men are not using PrEP–The role played by lack of interest in learning more about PrEP. Issue 1 (2nd January 2020) - Klein, Hugh; Washington, Thomas Alex
Abstract: Purpose: This paper examines lack of interest in pre-exposure prophylaxis (PrEP) and lack of willingness to use PrEP information sources among men who have sex with men (MSM). Methods: Demographic subgroups were compared via odds ratios in this purposive sample of 273 MSM. Results: 29% were uninterested in learning more about PrEP. Lack of interest was most common among: already PrEP-aware, Caucasian, HIV-positive, aged 40+, well-educated men. Most sources of information about PrEP were deemed unacceptable. Conclusions: Fueling the lack of PrEP use among MSM are a lack of interest in PrEP and an unwillingness to utilize existing information resources.